A hook on Patagonia: Spearthrowers, bone hook and grips from Patagonia - Scheinsohn, Vivian Gabriela (2016)
The present paper will evaluate the available evidence for the use of spearthrowers or atlatls in Patagonia based on the presence of a specific part of the equipment: the spearthrower hook or grip. This evidence will be contextualized through the review of the distribution and characteristics of spearthrower parts made from bone in the Southern Cone region of South America. The paper takes as its starting point a model created to define and identify the reasons behind the exploitation of osseous raw materials in Tierra del Fuego (Scheinsohn 1997, 2010). The model defined a period of experimentation, exploitation, and abandonment. Here, I will evaluate whether Patagonian bone spearthrower hooks and grips fit this model.